Review of Status of Post-Earthquake Reconstruction in Nepal (2015-2024): Challenges, Progress, and Future Directions - Parajuli, Navin; Adhikari, Samiksha (Journal of Advanced College of Engineering and Management, 2025)
In 2015, a powerful earthquake struck Nepal’s Gorkha District, causing extensive loss of life and property, and deeply affecting the nation’s infrastructure, housing, and cultural heritage. This disaster severely damaged Nepal’s rich cultural sites, with numerous temples and monuments either fully or partially destroyed. The loss of these heritage landmarks represented not only cultural devastation but also a profound impact on national identity and historical continuity. This article employs a qualitative approach, including critical literature review, field visits, interviews, document analysis, and case studies, to thoroughly examine the status of post-earthquake reconstruction efforts. The study focuses on key areas of reconstruction, such as housing, public infrastructure, and heritage restoration, offering an in-depth look at both progress and ongoing challenges. Although considerable advances have been made in rebuilding efforts, the earthquake highlighted Nepal’s need to strengthen building practices and disaster preparedness to better withstand future seismic events. Major obstacles in the reconstruction process include funding limitations, bureaucratic inefficiencies, corruption, logistical difficulties, governance issues, lack of coordination, limited accessibility, shortages of skilled labor, knowledge gaps, and the socio-cultural factors impacting rebuilding. This earthquake has underscored the urgency of revising building codes and adopting improved structural reinforcement methods to reduce future risks. Effective governance, inter-agency collaboration, and strategic incorporation of social and cultural dimensions are essential for continuing and sustaining the current reconstruction efforts in Nepal. Finally, the paper offers recommendations for strengthening Nepal’s post-earthquake recovery and resilience, focusing on institutional capacity building, coordination, and community based rebuilding strategies.